OnabotulinumtoxinA for the treatment of idiopathic overactive bladder is effective and safe for repeated use - Carlson, Kevin; Civitarese, Andrea; Baverstock, Richard (Canadian Urological Association Journal, 2017)
Introduction: The objective of this study was to compare efficacy and safety outcomes between patients receiving onabotulinumtoxinA (OnabotA) for the first time and those receiving a repeat injection. Methods: Data collected before and after OnabotA injection were extracted from a clinical registry. Patients were classified into either first or repeat injection subgroups. Efficacy was measured by the change in use of oral bladder medications, the number of voids per day or night, the frequency of urinary incontinence (UI) episodes, and patient-reported outcomes. Safety was measured by the number of self-reported complications. Differences in safety measures between the subgroups were tested. Results: The analysis included complete data from 81 patients; 30 (37%) receiving OnabotA for the first time, 51 (63%) receiving a repeat injection. Both subgroups reported significant reductions in the use of anticholinergics, more tolerable bladder symptoms, and improvements in patient-reported outcomes. Dry rates were similarly high in both groups (50% and 43%, respectively). There were no statistically significant differences between the subgroups in terms of their safety outcomes. Conclusions: OnabotA is equally as efficacious and safe for patients with overactive bladder receiving a repeat injection as it is for those receiving their first injection.